Virus containment box for retinopathy of prematurity screening and laser - Nayak, Sameera (Indian J Ophthalmol, 2021)
PURPOSE: Health care workers are susceptible to contracting infection with COVID-19 by aerosol transmission. This is a risk while examining and/or treating an un-sedated neonate in retinopathy of prematurity (ROP) screening and treatment. But screening for neonates for ROP and treating with laser, when required, should not be delayed to avoid the blindness. We describe a cost-effective method of containing aerosols generated during such a procedure in an un-sedated baby. METHODS: An acrylic transparent containment box was prepared to accommodate an average-sized infant. The box had four walls and a roof. The floor was open to place the container box over the baby. The walls have two types of openings, large ones to allow passage of hands to examine the baby, small ones to enable passage of oxygen tubing when required. A simulation was created to examine the impact of aerosol spray on examining healthcare personnel. RESULTS: The cost of the acrylic box was negligible. It could be assembled locally with available acrylic sheets and craftsmen. It was not difficult to examine the baby inside the box, and the simulation demonstrated that it protected the health personnel from the aerosol contamination. CONCLUSION: The described method is likely to increase healthcare personnel's confidence not to delay or deny ROP screening and laser treatment and save the babies from blindness.